Montmorillonitas modificadas com grupos funcionais orgânicos contendo enxofre e/ou nitrogênio e suas aplicações adsortivas e antimicrobianas - Santos, Saloana Santina Gomes (2019)
Clay minerals, such as montmorillonite (MMT), have been applied to remove toxic compounds from the environment. Although MMT has little interaction with anionic compounds, its adsorptive properties change after chemical modification. In this work, two bentonite samples (BENTx, x = 1, 2) with cation exchange capacities of 88.2 and 72.8 cmol (+) Kg-1 reacted with ethylene sulfide (S), ethylenediamine (en), 3 - aminopropyltrimethoxysilane and mercaptopropyltrimethoxysilane, whose compounds were applied as adsorbents for remazol blue and yellow dyes removal from aqueous solution and as antibacterial agents after copper (II) incorporation. The solids were characterized by X-ray diffraction (XRD), infrared (IR) spectroscopy, CHN elemental analysis, thermogravimetry (TG), scanning and transmission electron microscopy (SEM and TEM) and contact angle and wetting measurements. In dye adsorption tests parameters such as pH, adsorbent dosage, reaction time and initial dye concentration were evaluated. The solids obtained after the reaction with ethylene sulfide, spacing spacing (d001) of the MMT changed from 1.25 nm to 1.54 and 1.42 nm for BENT1-S and BENT2-S solids, respectively, indicating the intercalation. of organic moities. After the subsequent reaction with ethylenediamine, the basal spacing of the MMT was 1.34 and 1.31 nm for BENT1-S-en and BENT2-S-en, respectively. Infrared spectra (FTIR) presented new bands at 2934 and 2855 cm-1 attributed to CH asymmetric and symmetrical stretching, respectively. The results of CHN and thermogravimetry suggest the immobilization of ethylene sulfide and ethylenediamine in the bentonites. Adsorption tests for Remazol blue and yellow at pH 6.8 suggested maximum removal of 42.5 and 64.8 mg g-1 in BENT1-S-en in 300 min and 40.3 and 43.1 mg.g-1 for BENT2-S-en in 450 min. BENT1-AP and BENT1-MPTMS solids originated intercaltion hybrids with basal spacing of 1.85 and 1.36 nm, respectively. After interaction with ethylene sulfide, the carbon percentages were 13.86% and 20.24% for BENT1-MPTMS-S and BENT1-AP-S, respectively, suggesting the proposed immobilization. Wetting measurements indicated the formation of hydrophobic materials with contact angles around 100º. The indicated solids were saturated with copper (II) ions and applied as antimicrobial agents against the Staphylococcus aureus bacteria whose inhibitory concentration values were 50 and 25 mg mL-1 for the indicated materials with mercaptopropil and aminopropyltrimethoxysilane, respectively and for bentonite saturated with 50 mg mL-1 copper (II) ion. BENT2 sample interacted with ethylene sulfide in two consecutive reaction steps possibly leading to exfoliated material after the second reaction. The various proposed reactions originated bentonite hybrid materials for their use as adsorbents and antimicrobial materials.